Assessment of university students' financial management skills and educational needs - Falahati, Leila; Paim, Laily; Ismail, Maimunah; Haron, Sharifah Azizah; Masud, Jariah (Academic Journals, 2011)
The main aim of this study is to assess university students’ financial management skills and financial education needs. Data were collected among Malaysian public and private university students. Samples were selected using multi stage stratified sampling techniques. A total of 11 universities were randomly selected for the study and 350 questionnaires (300 for in campus and 50 for off-campus students) were distributed to students through the student affairs divisions of the respective universities. Perceived financial management skills were measured using a 5-point Likert scale from 1 (no skill at all) to 5 (very skilful) on 11 management related items: daily expenses, debt, future needs, time, savings, use of education loan, social interaction, stress, decision making, problem solving and career planning. The scores for the financial management skills were computed and the results revealed significant differences in the mean score among ethnic groups, with Chinese students scoring the lowest compared to other ethnic groups; public university students were perceived to have higher financial management skills compared to private university students; however, there was no gender difference in the score. Concerning the financial education needs, students indicated that they needed training related to career planning.